Exploring the social justice work of early childhood educators. Issue 5 (June 2019) - Nolan, Andrea; Lamb, Stephen
With the importance of the early years of a child's life to their learning and development, it is important that early childhood educators are skilled, reflective professionals who have the ability to actively support the learning of all children. Using a capability approach to human development as an evaluative framework, this article explores how early childhood educators across three early childhood services understand and take up the challenge of catering for diversity in children's learning. Educators with a social justice outlook are acknowledged as believing in the capacity of all children to succeed despite the circumstances of their lives or their abilities. While there are many real strengths that the educators in this study are saying, observing, reflecting on and doing, none of the educators mentioned children from socio-economically disadvantaged backgrounds as targets of their social justice work. The call is for educators to be more reflective of themselves and their practice to bring into focus the 'unchallenged' related to decision-making and professional judgements about programs and pedagogy, the 'unseen' such as children from underprivileged backgrounds, and the 'under-valued' being their own capabilities or those of their colleagues that remain untapped in their social justice work in relation to young children's learning and development. This research aims to raise awareness of the need for educators to consider the context within which they work and what this may mean for the experiences and situations of the children with whom they work.